(untitled) - Burke, Michael (Boca Raton, FL, 2009)
Nanotechnology: The Business presents an in-depth discussion of available corporate structures, delineating the advantages and disadvantages of each. It also describes an array of other issues the nano entrepreneur will encounter, from business plans and financing to budgeting, facilities procurement, and staffing.
Keywords: Nanotechnology,Công nghệ nano; Industrial applications,Ứng dụng công nghiệp